A radiotherapy staff experience of gratitude during COVID-19 pandemic. (June 2021) - Marconi, Elisa; Chiesa, Silvia; Dinapoli, Loredana; Lepre, Elisabetta; Tagliaferri, Luca; Balducci, Mario; Frascino, Vincenzo; Casà, Calogero; Chieffo, Daniela Pia Rosaria; Gambacorta, Maria Antonietta; Valentini, Vincenzo
Highlights: Medical staff from oncology units are at high risk of burnout during COVID-19 pandemic. The sense of belonging to the group and the contacting emotions play a central role in reducing these risks. Gratitude is related to well-involving people who practice and receive it. During lockdown, we adopted gratitude-focused "inter-group contact" tool.